The difficulty of the postural control task affects multi-muscle control during quiet standing - García-Massó, X. (Exp Brain Res, 2016)
The aim of this study was to compare the electromyographic (EMG) coherence between the lower limb and the core muscles when carrying out two postural tasks at different difficulty levels. EMG was recorded in 20 healthy male subjects while performing two independent quiet standing tasks. The first one involved a bipedal stance with the eyes open, while the second consisted of a dominant unipedal stance also with the eyes open. The obtained EMG signals were analysed by computing estimations of EMG–EMG coherence between muscle pairs, both singly (single-pair estimations) and combined (pooled estimations). Pooled and single coherence of anterior, posterior, core, antagonist and mixed pairs of muscles were significant in the 0–5 Hz frequency band. The results indicate that core and antagonist muscle groups, such as the anterior and posterior muscles, share low-frequency neural inputs (0–5 Hz) which could be responsible of the M-modes assembly. The core muscles could therefore provide the necessary synergy to maintain spine stability during the balancing exercise. Finally, differences in EMG–EMG coherence suggest that the muscle synergies formed during unipedal stance tasks are different from those established during bipedal stance. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00221-016-4602-z) contains supplementary material, which is available to authorized users.